Comparison of core temperature using tracheal thermometer and pulmonary artery catheter in adult patients undergoing coronary artery bypass graft surgery - Seyeon Park; Hee Young Kim; Hye-Jin Kim; Jieun Jung; Seo-Ho Hong; Yeon-Soo Jung; Dong-Hyeon Ha; Da-Eun Park; Ji-Uk Yoon (PLoS ONE, 2025)
Background Monitoring core temperature is important for patients under anesthesia. Esophageal and pulmonary artery blood temperatures can be used for measuring core temperature during general anesthesia. However, these methods pose challenges, especially when the placement of an esophageal thermometer and pulmonary artery catheter (PAC) is either impractical or not the preferred approach. An endotracheal tube (ETT) with a thermometer on the cuff allows for the measurement of tracheal temperature, providing a suitable alternative to core temperature measurement. This study aimed to assess the clinical reliability and accuracy of the thermometer in the ETT in comparison to the core temperature measured using a PAC. Methods Eleven patients who underwent coronary artery bypass graft (CABG) surgery were enrolled in this study. The patients were intubated using an ETT equipped with a thermometer on the cuff, and a PAC was inserted. Temperature measurements of both the trachea and pulmonary artery blood were recorded at 5-minute intervals for 1 hour before starting cardiopulmonary bypass. The agreement between the two temperature measurement methods was investigated using the Bland-Altman plot with multiple measurements per subject, and the correlation was evaluated using the concordance correlation coefficient (CCC). Results Eleven patients with a total of 143 pairs of data were included for analysis. The mean difference between the tracheal and pulmonary artery temperatures was −0.10°C. The 95% limit of agreement (LoA), calculated as ± 1.96 standard deviation, ranged from −0.35°C to 0.15°C. The 95% confidence interval for the lower and upper LoA was −0.51°C to −0.27°C and 0.07°C to 0.31°C, respectively. The maximum allowed difference (Δ) was set at 0.5°C. The majority of temperature differences fell within the LoA and were well below the maximum allowed difference. The CCC was 0.95, which indicates a substantial strength of agreement. Conclusions The agreement between the tracheal and pulmonary artery temperature measurements using the ETT thermometer and pulmonary artery catheter, respectively, was found to be clinically reliable and accurate. Therefore, the tracheal temperature measurement can effectively represent the core temperature of the patients. Employing an ETT equipped with a thermometer on the cuff can serve as a reliable and independent method for measuring core temperature. Trial registration Clinical trial registration number: NCT05595616.